Directing treatment of the concept of cruelty in the Iraqi theater show (Autumn play as a specimen) (Journal of the College of Basic Education, 2022)
Cruelty has accompanied man since ancient times, and it has often been confused with violence due to the intensity of the closeness between them, and here the research tries to separate both concepts and is unique to the concept of cruelty, which was highlighted in the theater for the first time by the French (Antoine Artaud) in an attempt to reveal the directing treatment that It was presented by the Iraqi director (Sameem Hasaballah) to the concept of cruelty in his tagged play (Autumn).